A trans‐omics assessment of gene–gene interaction in early‐stage NSCLC - Jiajin Chen; Yunjie Song; Yi Li; Yongyue Wei; Sipeng Shen; Yang Zhao; Dongfang You; Li Su; Maria Moksnes Bjaanæs; Anna Karlsson; Maria Planck; Johan Staaf; et al. (Molecular Oncology, 2023)
Epigenome‐wide gene–gene (G × G) interactions associated with non‐small‐cell lung cancer (NSCLC) survival may provide insights into molecular mechanisms and therapeutic targets. Hence, we proposed a three‐step analytic strategy to identify significant and robust G × G interactions that are relevant to NSCLC survival. In the first step, among 49 billion pairs of DNA methylation probes, we identified 175 775 G × G interactions with PBonferroni ≤ 0.05 in the discovery phase of epigenomic analysis; among them, 15 534 were confirmed with P ≤ 0.05 in the validation phase. In the second step, we further performed a functional validation for these G × G interactions at the gene expression level by way of a two‐phase (discovery and validation) transcriptomic analysis, and confirmed 25 significant G × G interactions enriched in the 6p21.33 and 6p22.1 regions. In the third step, we identified two G × G interactions using the trans‐omics analysis, which had significant (P ≤ 0.05) epigenetic cis‐regulation of transcription and robust G × G interactions at both the epigenetic and transcriptional levels. These interactions were cg14391855 × cg23937960 (βinteraction = 0.018, P = 1.87 × 10−12), which mapped to RELA × HLA‐G (βinteraction = 0.218, P = 8.82 × 10−11) and cg08872738 × cg27077312 (βinteraction = −0.010, P = 1.16 × 10−11), which mapped to TUBA1B × TOMM40 (βinteraction =−0.250, P = 3.83 × 10−10). A trans‐omics mediation analysis revealed that 20.3% of epigenetic effects on NSCLC survival were significantly (P = 0.034) mediated through transcriptional expression. These statistically significant trans‐omics G × G interactions can also discriminate patients with high risk of mortality. In summary, we identified two G × G interactions at both the epigenetic and transcriptional levels, and our findings may provide potential clues for precision treatment of NSCLC.